Analisa Pola Dan Spektrum Partial Discharge Terhadap Kerusakan Transformator - Togi Sugiono; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Electrical system is one very important part in industry.Partial discharge is a disturbance phenomenon thatoccurs in power transformers. When partial discharge conducted continuously it will damage thetransformer. Partial discharge Measurement on the transformer in PT. IKPP is conducted to determine thecondition of the transformer insulation resistance, by analyzing the shape of the wave pattern and spectrumaccording to the standard used. The method uses Power PD-TP500A along with the Acoustic Emission (AE)sensor and the High Frequency Current Transducer (HFCT) sensor measurement on 3 33KV transformersand analyze the pattern and the spectrum using software Power PD-TP500A MD. The measurement of the1st transformer on Tuesday, September 17th 2019 at 02:25 pm resulted there was no formation of wavepatterns and spectrum and indicated normal transformer. The measurement of the 2nd transformer onThursday, September 19th 2019 at 2:10 pm resulted there was the formation of wave patterns and spectrumindicating monitoring level condition. Then the measurements of the 3rd transformer on Monday, September2019 at 2:30 pm resulted there was formation of wave patterns and spectrum on the AE and HFCT sensorsindicating critical level condition. The normal, monitoring and critical condition of a transformer can bestated using partial discharge pattern and shape analysis done in this research.Keywords: Transformer Partial Discharge, Power PD-TP500A, AE Sensor, HFCT Sensor